Skills Acquired during Teacher Training Programs (B.Ed & M.Ed) and Skills Required in Actual Classroom - zain ul abdin (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The aim of this study was to explore the differences between the skills developed in teacher training programs and the skills used in the classrooms. The population of this study was 937 Head Masters BPS-17 selected through IBA Sukkur. These Head Masters were selected for primary and Elementary schools by the government of Sindh. Data was collected from the participants through simple random sampling. The sample size for this study was 187 IBA Head Masters all over the Sindh. The questionnaire was used as a research tool to get the responses from IBA selected Head Masters about their teachers who are teaching in their schools.  Data was analyzed through descriptive statistics. Participants’ responses were analyzed through percentage, mean, and standard deviation. The mean score shows that the majority of teachers don’t have planning (M= 2.31), presentation (M=2.29), and management skills (2.34). The mean score of command over the subject factor is (M= 2.02), appropriate teaching methodologies factor (M= 2.28) and evaluation skills factor (M= 2.22) shows that majority of teachers don’t have command over the subject and they do not use appropriate and modern teaching methodologies. Furthermore, teachers do not have evaluation skills to measure the students learning objectives and to know the students' strengths and weaknesses. It was concluded that whatever teachers learned in the professional trainings do not use those skills in the classrooms because most teachers are not interested in teacher training programs.